2017
DOI: 10.1590/1518-8345.1337.2857
|View full text |Cite
|
Sign up to set email alerts
|

Comparison among the efficacy of interventions for the return rate to receive the pap test report: randomized controlled clinical trial

Abstract: Objective: to test the effects of a behavioral, an educative and a comparative intervention on women's adherence to the return appointment to receive the pap test report. Methods: randomized controlled clinical trial at a Primary Health Care Service, involving three groups: EG (educative session and test demonstration), BG (recall ribbon) and standard intervention (card containing the return appointment -graphical reminder), called comparative group here (CG). To select the sample, the following was establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Yet, few studies have focused on the role that patient navigation might play in cancer care in LMICs or on how these services can affect health outcomes in countries with fragmented or fragile health systems. In the 14 studies included in the review, the types of patient navigation services that were offered mirrored those provided in HICs, notably facilitating linkages to follow-up services [6, 3135], providing counselling [6, 33, 34, 3639], providing financial support [40], coordinating appointments [32, 33, 35, 39–43], and maintaining communication with patients and families [40, 41, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, few studies have focused on the role that patient navigation might play in cancer care in LMICs or on how these services can affect health outcomes in countries with fragmented or fragile health systems. In the 14 studies included in the review, the types of patient navigation services that were offered mirrored those provided in HICs, notably facilitating linkages to follow-up services [6, 3135], providing counselling [6, 33, 34, 3639], providing financial support [40], coordinating appointments [32, 33, 35, 39–43], and maintaining communication with patients and families [40, 41, 43].…”
Section: Discussionmentioning
confidence: 99%
“…In a separate intervention study, undertaken in Fortaleza, the educational group (a flip chart in the waiting room) presented a non-return rate of 18%, while the behavioral group (who were given a bracelet with the return date printed on it) had a rate of 34%, and the comparison group, one of 23%. The bracelet for reminding the service users of the date did not bring any benefits, but, rather, contributed to distancing the women from the service 12 . As a result, the interventions tested in the present study were shown to be more simple and efficacious for motivating the women to attend to collect the report.…”
Section: Discussionmentioning
confidence: 99%
“…Group 2 - telephone call - educational intervention: as well as the normal attendance, the women were offered an intervention in the form of an educational telephone call, whose content was guided by the themes from script-file 4 from technology developed in a previous study 12 and based in the Brazilian guidelines for controlling cervical cancer. The dialogue established in the telephone approach was conducted according to the principles of the Motivational Interview (MI).…”
Section: Methodsmentioning
confidence: 99%
“…In a study of Brazilian women undergoing cervical cancer screening through Papanicolaou testing at a single urban center ( n = 775), patients were randomized to either receive a written card with a follow-up date on it (control), education on the importance of returning to the clinic and follow-up for the results (education), or a novel patient navigation method where different colored wristbands with reminders were tied onto the wrists of patients (navigation group). The navigation group had a lower follow-up rate (66%) than both the education group (82%) and the control (77%) ( P < 0.05)[ 39 ]. This highlights the importance of studying the interventions prior to implementation as not all interventions are acceptable, feasible, or produce the same results given differences in the clinical and cultural context of the healthcare system and the community.…”
Section: Patient Navigation and Community Health Workersmentioning
confidence: 99%